Competition and the financial crisis (OECD [Paris]FR, 2009)
Discusses the role of competiotion policy in times of systemic financial crises. Focuses primarily on the financial sector, but also discusses the applicability of competition policy to the real sector.
Keywords: COMPETITION POLICY